Alkaline and acid phosptiatases in different tissues of Channa punctatus exposed to metanil yellow - Sharma, S D; ., Maya (Indian Journal of Fisheries, 2011)
The live specimens of Channa punctatus were procured from the nearby water bodies and acclimatized to laboratory conditions (temperature 22°±2°C, pH 6.8, D.O. 7 mg/ litre, hardness 6.6 mg/litre, total solids 21.6 mg/litre) for one week. Then 80 healthy fishes of weight group 40-60 g were selected irrespective of their sex and washed with 0.1% KMnO^ solution, prior to experimentation, to avoid any external infection. The toxicant metanil yellow, was used during the present investigation.